(3OjhGf NWH GHf fHGJgs - (3GdLPGej GdaGQbqj GdeUQj, CHh HcQ, GHf fHGJI, LeGd GdOjf, eMeO Hf eMeO Hf eMeO Hf GdMSf, J (B768(3g`s ((3CMeO Hf eMeO PjHs)
(3ChdgG (B:s
(3agPG OjhGf YXje aj GdNWH LYdJg Ydi LejY YOO GdSfI Cbhd hHGddg GdJhajb GdNWHI GdChdi deMQe(B: (3GdMeO ddg eLOO GdCYhGe YGeG HYO YGe GdPj GaJJM HCaVd GdCTgQ TgQ GdeMQe gPG GdYGes
(3BNQgG (B:s
(3hCcJH GdSdGeI hGdYGajI YdjfG hYdjce (B((3cPG(B) (3hYdi SGFQ GdMLGL hGdZRGI hGdeSGaQjf hGdeQGHWjf aj HQc hHMQc ef GdeSdejf jG QH GdYGdejf YHGO Gddg Ef Gddg jCeQ HGdYOd hGdEMSGf hEjJGA Pj GdbQHi hjfgi Yf GdaMTGA hGdefcQ hGdHZj jYXce dYdce JPcQhf GPcQhG Gddg jPcQces
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 38s
(3eYLe GdeDdajf(B: 3 / 676s
(3cTa GdXfhf(B: 1 / 714s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs